The Vulnerability to Suicidal Behavior is Associated with Reduced Connectivity Strength - Bijttebier, Stijn; Caeyenberghs, Karen; van den Ameele, Hans; Achten, Eric; Rujescu, Dan; Titeca, Koen; van Heeringen, Cornelis (Frontiers in Human Neuroscience, 2015)
Suicidal behavior constitutes a major public health problem. Based on the stress–diathesis model, biological correlates of a diathesis might help to predict risk after stressor-exposure. Structural changes in cortical and subcortical areas and their connections have increasingly been linked with the diathesis. The current study identified structural network changes associated with a diathesis using a whole-brain approach by examining the structural connectivity between regions in euthymic suicide attempters. In addition, the association between connectivity measures, clinical and genetic characteristics was investigated. We hypothesized that suicide attempters showed lower connectivity strength, associated with an increased severity of general clinical characteristics and an elevated expression of short alleles in serotonin polymorphisms. Thirteen euthymic suicide attempters (SA) were compared with fifteen euthymic non-attempters and seventeen healthy controls. Clinical characteristics and three serotonin-related genetic polymorphisms were assessed. Diffusion MRI together with anatomical scans were administered. Preprocessing was performed using Explore DTI. Whole brain tractography of the diffusion-weighted images was followed by a number of streamlines-weighted network analysis using NBS. The network analysis revealed decreased connectivity strength in SA in the connections between the left olfactory cortex and left anterior cingulate gyrus. Furthermore, SA had increased suicidal ideation, hopelessness and self-reported depression, but did not show any differences for the genetic polymorphisms. Finally, lower connectivity strength between the right calcarine fissure and the left middle occipital gyrus was associated with increased trait anxiety severity (rs=-0.78, p<0.01) and hopelessness (rs=-0.76, p<0.01). SA showed differences in white matter network connectivity strength associated with clinical characteristics. Together, these variables could play an important role in predicting suicidal behavior.